1981
DOI: 10.1007/bf02582391
|View full text |Cite
|
Sign up to set email alerts
|

Soya protein and athersclerosis

Abstract: Cholesterol‐free, semipurified diets produce hypercholesterolemia and atherosclerosis in rabbits when casein is used as dietary protein, but not when the casein is replaced by soya protein. In general, animal proteins produce higher levels of plasma cholesterol in rabbits than plant proteins. At least part of this difference appears to be related to differences in the amino acid composition of the proteins. Rabbits fed soya protein had a faster turnover of plasma cholesterol, absorbed cholesterol from the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Although Kritchevsky (65) suggested that the lysine/arginine ratio was important, experimental studies by others failed to show a correlation (66). Lysine and branched chain amino acids (leucine, isoleucine, and valine) were associated with hypercholesterolemia and hypertriglyceridemia (38,67,68) in humans and rats.…”
Section: Discussionmentioning
confidence: 96%
“…Although Kritchevsky (65) suggested that the lysine/arginine ratio was important, experimental studies by others failed to show a correlation (66). Lysine and branched chain amino acids (leucine, isoleucine, and valine) were associated with hypercholesterolemia and hypertriglyceridemia (38,67,68) in humans and rats.…”
Section: Discussionmentioning
confidence: 96%
“…JML powder contains protein, lipid and chlorophyll in addition to DF. Then, involvement of these components should not be disregarded in studying the effective component for suppressing the serum TC elevation as vegetable protein such as soybeans (12)(13)(14)(15) and chlorophyll (its derivatives) (16) are known to be effective for decreasing serum TC. However, despite a high protein content in the residue after extraction with water, a cholesterol-lowering effect was not seen.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a large body of literature on casein consumption and heart disease in animals [11][12][13]. Casein has been recorded as causing heart disease, or hypercholesterolaemia, in rabbits [14][15][16][17][18][19][20], rats, pigs [21] and monkeys [22,23].…”
Section: Milk Consumption and Ihdmentioning
confidence: 99%